Longterm effects of compression method in the surgical treatment of bleeding haemorrhoids (Bangladesh Journal of Medical Science, 2013)
Objective: Present study was undertaken to find out the long term effect of application of compression probe after haemorrhoidectomy in the treatment of bleeding haemorrhoids. Materials and methods: They study was carried out in the Department of Clinical Surgery, Russian People's Friendship University, Moscow, Russia, from January 1992 to December 2001, on 80 patients, equally divided into two groups, case (haemorrhoidectomy plus application of compression probe) and control (haemorrhoidectomy only). Results: Long term follow up showed higher good outcome in case group (82.1%) compared to control (53.8%) (P